Diabetic Ketoacidosis in Pregnancy: A Systematic Review of the Reported Cases - Dimitra Stathi; Florence Ning Lee; Mili Dhar; Stergios Bobotis; Elisavet Arsenaki; Taruna Agrawal; Konstantinos Katsikas Triantafyllidis; Konstantinos S Kechagias (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: Diabetic ketoacidosis (DKA) is a rare but serious complication that can develop during pregnancy, with up to 30% of patients presenting with euglycemia, making prompt recognition challenging. It is associated with increased perinatal mortality rates, although the exact risk of maternal mortality remains unclear. The purpose of this systematic review was to examine the available literature and provide an overview of reported cases of DKA during pregnancy. Methods: PubMed, Web of Science and Scopus library databases were screened from inception until January 2024. Included studies provided data on classic or euglycemic DKA during pregnancy. All study designs were considered eligible for inclusion. Results: We identified 66 eligible articles, which included 57 case reports and case series with individual patient data, and 9 studies without individual patient data. The mean age at diagnosis was 28.8 years, and the average gestational age at diagnosis was 29.5 weeks. The majority of women had type 1 diabetes mellitus (T1DM) (45.9%), followed by gestational diabetes (GDM) (40.5%). Most cases were classified as classic DKA (70.3%), with nearly one-third developing euglycemic DKA (29.7%). The most common trigger factors were infections (28%), followed by poor adherence to treatment (13.5%). The most frequent symptoms included nausea (32.4%), vomiting (32.4%), osmotic symptoms (21.6%), and abdominal pain (20.2%). All cases were treated with intravenous insulin and fluids. The vast majority (98.9%) of women eventually fully recovered, with only 1 reported death due to organ failure (1.3%). Intrauterine death or stillbirth occurred in one-third of cases (35.2%), including 1 instance of a twin pregnancy. Conclusions: DKA is a condition that clinicians may encounter during pregnancy. Although rare, increased awareness and early recognition are crucial for optimal management and improved maternal and neonatal outcomes.